Gender Discrimination in Nepal - Anil Kumar Gupta; Poonam Kumari Kanu; Bishnu Prasad Lamsal (Advanced Studies on Socio-Economy Development, 2021)
Gender discrimination is a pressing issue in gender research across the globe. While the Government of Nepal has taken several measures to address gender discrimination it remains prevalent at all levels of society. This paper examines the prevalence of gender discrimination in Nepal and its variability based on socio-demographic status. It employs micro-level data generated by Nepal National Governance Survey 2017/18 was used and analyzed through a logistic regression model. The results showed that the experience of gender-based discrimination varies based on socio-demographic factors including: gender, age, urban/rural, education, and economic status. Women’s experiences of discrimination or marginalization vary based on their intersectional identity. The deeply ingrained patriarchal gender ideology in Nepal, driven by traditional cultural values and practices, perpetuates discrimination along gender lines. Keywords: Discrimination, Gender, Patriarchal, Women, Nepal.